(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The Mahalla, a centuries-old neighborhood self-governance institution in Uzbekistan, currently stands at a critical juncture between preserving its traditional social fabric and responding to the imperatives of a modernizing state. This article undertakes a comprehensive examination of the theoretical and practical foundations necessary for introducing contemporary management methodologies into Mahalla institutions without undermining their unique communal essence. Employing a qualitative, multi-case study design across four Mahallas in Tashkent and Fergana regions, the research draws upon in-depth interviews with Mahalla chairs, activists, and local government officials, as well as document analysis and direct observations conducted over an eight-month period. The study identifies a profound tension between the deeply embedded informal, consensus-driven management traditions and the principles of strategic planning, performance measurement, digitalization, and participatory budgeting advocated by modern public administration paradigms. Findings reveal that while there is a palpable demand for increased efficiency, transparency, and service quality, the wholesale import of New Public Management tools provokes resistance rooted in fears of cultural erosion and the disruption of organic solidarity networks. Conversely, a hybridized approach, which strategically integrates elements of agile management, digital communication platforms, and results-oriented frameworks within the existing socio-cultural architecture, demonstrates considerable promise. The article contributes an original conceptual model—the Culturally Anchored Modernization Framework—that outlines a phased, context-sensitive pathway for reform, emphasizing capacity building, co-design with community elders, and the incremental introduction of managerial innovations. The practical implications of this study offer a roadmap for policymakers and international development partners seeking to strengthen local governance in Uzbekistan and analogous post-Soviet community institutions, ensuring that modernization reinforces rather than erodes the Mahalla’s vital role as a pillar of social cohesion.